2014
DOI: 10.1371/journal.pone.0106434
|View full text |Cite
|
Sign up to set email alerts
|

Search for MicroRNAs Expressed by Intracellular Bacterial Pathogens in Infected Mammalian Cells

Abstract: MicroRNAs are expressed by all multicellular organisms and play a critical role as post-transcriptional regulators of gene expression. Moreover, different microRNA species are known to influence the progression of a range of different diseases, including cancer and microbial infections. A number of different human viruses also encode microRNAs that can attenuate cellular innate immune responses and promote viral replication, and a fungal pathogen that infects plants has recently been shown to express microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 45 publications
3
82
0
Order By: Relevance
“…Overall, this study provides an association between a specific miR (miR‐214), and its target gene ( ICAM1 ) in early stage C. muridarum infection. This study not only provides evidence of miR‐214‐dependent regulation of ICAM1 , which probably contributes to infiltration of neutrophils and pathology, but also augments the body of evidence supporting the regulatory role of miRs in Chlamydia pathogenesis . Possible ICAM1 regulation by miR‐214 was first suggested in C. muridarum ‐infected genital tract tissues (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Overall, this study provides an association between a specific miR (miR‐214), and its target gene ( ICAM1 ) in early stage C. muridarum infection. This study not only provides evidence of miR‐214‐dependent regulation of ICAM1 , which probably contributes to infiltration of neutrophils and pathology, but also augments the body of evidence supporting the regulatory role of miRs in Chlamydia pathogenesis . Possible ICAM1 regulation by miR‐214 was first suggested in C. muridarum ‐infected genital tract tissues (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Transcriptome-wide or sequencing approaches have revealed the role for specific immune genes and associated pathways following infection with Ct-plasmid-sufficient and -deficient strains (Porcella et al 2015; Carlson et al 2008; Ferreira et al 2013; Qu et al 2015). Similarly, regulatory genetic species, namely microRNAs of bacterial and host origin have revealed the role(s) in growth and cellular function following infection (Derrick et al 2013; Furuse et al 2014; Gupta et al 2015; Yeruva et al 2014; Igietseme et al 2013). Proteomic studies have identified immunodominant, T- and B cell chlamydial antigens involved in primary infection and vaccination (Cruz-Fisher et al 2011; Wang et al 2010; Karunakaran et al 2015; Picard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that bacteria could also produce functional miRNA or miRNA-like snRNAs (12,13). In this study, we found that Wolbachia, as endosymbiotic bacteria, are able to encode snRNAs that act as effectors to modulate the expression of Wolbachia and mosquito host genes.…”
mentioning
confidence: 68%